Integrating Smart Tourism and Creative Economy: Toward an Adaptive Governance Model for Sustainable Rural Destinations - Kurniadi K Hasan; Mohamad Fadly Binolombangan (Universitas Teuku Umar, 2026)
This study aims to analyze the development of the Perintis Lake tourist area in Bone Bolango Regency, Gorontalo Province, through the integration of smart tourism and the creative economy as a policy strategy towards inclusive and sustainable tourism. This study reflects a paradigm shift from solely economic-based tourism to governance oriented toward technology, creativity, and community empowerment. The research method used descriptive qualitative methods, with primary data derived from observations, in-depth interviews, and focus group discussions and secondary data from policy documents and scientific literature. The results indicate that the implementation of smart tourism in Perintis Lake is still limited by digital infrastructure and community technological literacy, while the creative economy is developing organically through MSMEs and Tourism Awareness Groups. The relationship between the two is symbiotic: digital technology expands markets and accelerates the promotion of local products, while the creative economy enriches cultural content and digital tourism experiences. The study formulated the Integrated Smart Creative Lake Tourism Model (ISCLTM), which integrates Smart Experience, Smart Business Ecosystem, Smart People, and Smart Governance within an adaptive feedback loop mechanism. This model emphasizes that destination competitiveness arises from the synergy of technological innovation, social creativity, and collaborative policies, not solely from digitalization.